What's in a name?: shifting identities of traditional organized crime in Canada in the transnational fight against the Calabrian 'Ndrangheta - Sergi, Anna (Canadian journal of criminology and criminal justice, 2018)
The Italian antimafia authorities have warned Canadian law enforcement about the risks and the growing concerns for the infiltration of clans of the Calabrian mafia, known as 'ndrangheta, in Eastern Canada. The alarm linked to the rise of the 'ndrangheta challenges the paradigms of traditional organized crime in Canada, because the 'ndrangheta is presented as traditional but also innovative and more pervasive than other mafia-type groups. Through access to confidential investigations and interviews of key specialist law enforcement teams in Toronto and Montreal, this article investigates today's institutional perception of mafia – the 'ndrangheta in particular – in Canada when compared to Italian conceptualizations. I will argue that the changes in narratives in Canada can be read in relation to changes in the Italian identity in the country, moving towards regionalization and specialist knowledge of ethnic differences.